Ethics: A Very Short Introduction - Simon Blackburn (Great britain Oxford university press, 2001)
Our self-image as moral, well-behaved creatures is dogged by scepticism, relativism, hypocrisy, and nihilism, by the fear that in a Godless world science has unmasked us as creatures fated by our genes to be selfish and tribalistic, or competitive and aggressive. In this clear introduction to ethics Simon Blackburn tackles the major moral questions surrounding birth, death, happiness, desire and freedom, showing us how we should think about the meaning of life, and how we should mistrust the soundbite-sized absolutes that often dominate moral debates.